PMT-scintillator system set up for DD neutron TOF measurements in INTI plasma focus device - Damideh, Vahid; Saw, S. H.; Sadighzadeh, Asghar; Jalil, Ali; Rawat, R. S.; Lee, P.; Lee, S. (AIP Publishing, 2017)
This paper summarizes a Photomultiplier-Scintillator diagnostic system for use in our plasma focus experiments at the Center for Plasma Research INTI IU. The system features an anode-grounded high pulse linearity voltage divider and uses NE102A plastic scintillators. It has detected D-D neutrons in INTI plasma focus device with clear and high signal to noise ratio. Neutron TOF of 120 ns has been measured from the time difference between hard x-ray pulse peak and neutron peak time over a flight path of 2.6±0.01 m; giving energy of 2.5±0.1 MeV for these side-on neutrons.